Defining potentials and barriers to trade in the Malaysia–Chile partnership - Devadason, Evelyn Shyamala; Chandran, V.G.R.; Mubarik, Shujaat (Elsevier, 2018)
Purpose: The purpose of this paper is to investigate the potentials and barriers to trade in the Malaysia–Chile partnership. Design/methodology/approach: This paper estimates two-way export potentials from an augmented three-dimensional panel gravity model of bilateral trade between Malaysia and the Latin America and the Caribbean (LAC) region, spanning the 1990–2014 period. Utilizing interviews with government officials and industry experts in Malaysia and Chile, this paper also provides insights into market access issues. Findings: The empirical findings of this study suggest that Malaysia has trade potential in Chile, but Chile is “overtrading” with Malaysia. By major products traded, both countries are found to be “overtrading,” as the export basket remains concentrated in this partnership. Through the interviews, fewer restrictions are reported by the various stakeholders, as the extent of trade engagement remains somewhat low. The main challenge identified within specific sectors in both the countries relates mainly to procedures established to secure compliance with labeling regulations for food products. Research limitations/implications: The sectoral findings reveal that there is indeed scope for expanding exports beyond the current major products traded, particularly in base metal and scientific and measuring equipment from the Malaysia and Chile perspectives, respectively. Thus, product diversification matters to intensify trade cooperation between the two countries. Non-tariff measures need to be streamlined by both parties to ensure further product diversification to food trade, particularly for Chile. Originality/value: The limited literature on cross-regional trade within the broader framework of Southeast Asia and LAC only support the fact that potentials do exist but do not appear to provide much research evidence. Empirically, this paper will add to the existing literature on the potentials that hold in the Malaysia–Chile partnership. Further, a lack of adequate information remains on market access and other barriers in both the nations to facilitate decisions on trade opportunities. The findings of the study fill that vacuum of information pertaining to market access and trade facilitation through interviews with various stakeholders in Malaysia and Chile.